The Nexus Between Financial Inclusion and Economic Growth in ASEAN - Suidarma, I Made (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
Inclusive growth has recently become an interesting issue to be studied more deeply, especially in the financial sector as outlined in the concept of financial inclusion. The role of the financial sector is important considering this sector is the primary sector in encouraging economic activity especially in the real sector. This study aims to analyze the influence and long-term relationship of financial inclusion through the instrument of the number of Automatic Teller Machine (ATM)s and commercial bank branches on ASEAN economic growth through Gross Domestic Product (GDP). The data used is secondary data in the form of an annual panel consisting of ASEAN countries with the period of 2008-2015 for the purpose of seeing the impact after the global crisis that occurred. The method used Panel Vector Error Correction Model (VECM) to see the long-term relationship and the GDP response when shocks occur in the variable financial inclusion. The result of estimation shows that financial inclusion through the number of ATMs and the number of branches of commercial banks were able to contribute positively to economic growth in ASEAN.